How Accessible is Education for Migrant Workers’ Children? : A Case Study of an On-site School - Yadav, Aarti (Voices of Teachers and Teacher Educators, 2021)
The interstate migration of construction workers has a significant impact on the education of their children. Their children are often deprived of educational facilities due to the interplay of several social and economic push factors. The present research is a case study of an onsite school serving migrant workers’ children and aims to know the educational status of migrant workers’ children and understand their educational problems. The qualitative data reveals several barriers in the educational path of migrant workers’ children such as low economic status of workers, safety concerns related to sending children to far off schools in migrated places, language barriers in school, lack of awareness about free education and other benefits provided in government schools and impoverished site school.